Hiding the unwanted: A University-level campus carry policy - Ruoppila Sampo (Springer, 2022)
Campus carry laws have allowed civilians to legally bring their concealed firearms onto college and university campuses in several states in the U.S. over the past decade. Previous studies have addressed the policy’s legal grounds, arguments for and against it, impacts on campus safety, and faculty and students’ attitudes toward it. This paper examines the less addressed topic of policy implementation, especially the role of universities in modifying the outcomes, including what kinds of rules the higher educational institutions themselves have designed and what these approaches mean. The article focuses on Texas, where public higher educational institutions were required to allow campus carry but also given some discretion in implementation. The article provides a qualitative content analysis of policy documents and expert interviews regarding the campus carry policy at The University of Texas at Austin. It argues that the university fully accomplishes the law, but through its policy it has also sought to hide it, removing the issue from everyday life on campus.